Broken places (Chigaco Mystery, ,, 2019)
Cops can make mistakes, even when they're not rookies. If anyone knows that it's Cass Raines. Cass took a bullet two years ago after an incompetent colleague screwed up a tense confrontation with an armed suspect. Deeply traumatized, Cass resigned from the Chicago PD, leaving one less female African-American on the force. Now she's the head of a one-woman private investigation agency, taking on just enough work to pay the bills. But when the only father figure she's ever known, Father Ray Heaton, asks her to look into a recent spate of vandalism at his church, she readily agrees to handle it. Only hours later Cass is horrified to discover Father Ray's murdered body in the chuch confessional, a dead gangbanger sprawled out nearby. She knew Pop, as she called him, had ticked off plenty of people, from slumlords to politicians, with his uncompromising defense of the downtrodden. But a late-night random theft doesn't seem like much of a motive at a cash-strapped parish. The lead detective assigned to the case is all to eager to dismiss it as a burglary gone awry, just another statistic in a violent city, but Cass's instincts tell her otherwise, and badge or no badge, she intends to see justice done...

Strange weather: four short novels (HarperCollins, William Morrow, an imprint of HarperCollinsPublishers, 2017)
"Snapshot" is the disturbing story of a Silicon Valley adolescent who finds himself threatened by "The Phoenician," a tattooed thug who possesses a Polaroid Instant Camera that erases memories, snap by snap. In "Loaded," a mall security guard in a coastal Florida town courageously stops a mass shooting and becomes a hero to the modern gun rights movement. But under the glare of the spotlights, his story begins to unravel, taking his sanity with it. When an out-of-control summer blaze approaches the town, he will reach for the gun again and embark on one last day of reckoning. A young man takes to the skies to experience his first parachute jump. . . and winds up a castaway on an impossibly solid cloud, a Prospero's island of roiling vapor that seems animated by a mind of its own in "Aloft." On a seemingly ordinary day in Boulder, Colorado, the clouds open up in a downpour of nails--splinters of bright crystal that shred the skin of anyone not safely under cover. "Rain" explores this escalating apocalyptic event, as the deluge of nails spreads out across the country and around the world. A collection of four short novels that take us beyond the ordinary, into dreams and nightmares. There's a tattooed thug whose camera erases memories; a young man on his first parachute jump becoming trapped on a cloud; a rain of crystal splinters that shred the skin of anyone not safely under cover; and a security guard who stops a mass shooting in a mall and becomes a hero until his story begins to unravel.
Snapshot , Loaded , Aloft , Rain.

Diamond solitaire (Peter Diamond mystery, 2,, 2007)
Private investigator Peter Diamond's search for a Japanese girl's identity leads to murder, drugs, and the Mafia.